Learning from environmental actors about environmental developments: the case of international organizations - Kathrin Böhling (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
This article makes a case for viewing international governmental organizations (IOs) as corporate agents capable of learning. In doing so, it attempts to go beyond prevailing conceptions of IOs as means or settings for multilateral negotiation and bargaining. The proposed theoretical framework argues from an organizational learning perspective. By integrating notions from neo-institutionalism and policyanalysis it tries to capture the impact of IOs' publicness on learning processes. The focus is on IOs' relations with stakeholders and constituencies for the development and implementation of transboundary policies. These interactions are seen as a means to learn about external demands, expectations and expertise. Their impact on the internal dynamics in IOs tends to be of a dual nature: enhanced adaptability in its margins and buffering the organizational core from environmental fluctuations. Hence, some skepticism is appropriate in assessing IOs' capacity to engage in profound changes as a result of learning. It rests on the contention that the social constitution of the organization-environment nexus and its linkages with intraorganizational processes is of crucial importance for IOs' ability to learn about environmental changes and developments. Emphasis is placed on the contested and controversial nature of knowledge absorption and the limiting effect of administrative routines and procedures on IOs' absorptive capacity. – – Im vorliegenden Aufsatz wird der Versuch unternommen, internationale gouvernmentale Organisationen als lernfähige korporative Akteure zu betrachten. Damit soll gezeigt werden, dass internationale Organisationen weder als Instrumente mitgliedstaatlicher Interessen noch als Arenen multilateraler Verhandlungsprozesse hinreichend verstanden werden können. In der Perspektive des Organisationslernens wird danach gefragt, wie internationale Organisationen im Zuge des Interaktionsgeschehens mit Akteuren aus ihrem Umfeld über äußere Veränderungen und Trends lernen. Dabei geht es um die Vermittlung als auch die Interpretation der von außen an internationale Organisationen herangetragenen Erwartungen, Anforderungen, Ideen und Wissen. Ziel des Papiers ist die Entwicklung eines theoretischen Analyserahmens, der das Interaktionsgeschehen zwischen internationalen Organisationen und den ihre Umwelt repräsentierenden Akteuren als Auslöser für organisationale Lernprozesse begreift und gleichzeitig auch institutionelle, kulturelle und politisch-interessenbezogene Bedingungen berücksichtigt. Die aus dem Spannungsfeld zwischen Organisation und Umwelt resultierenden Lernprozesse sind dualer Natur: Erhöhte Anpassungsfähigkeit in den Grenzbereichen internationaler Organisationen geht mit Abpufferung des Organisationskerns von Umweltfluktuationen einher. Diese Einschätzung gründet auf der Prämisse der sozialen Konstituierung des Organisations-Umwelt Nexus und dessen Verbindungen mit organisationsinternen Prozessen. Darüber hinaus wird die politische Bedingtheit organisationaler Wissensprozessierung und der Einfluss administrativer Routinen und Verfahren auf die Aufnahmefähigkeit internationaler Organisationen betont.
Keywords: 330; Internationale Organisation; Lernende Organisation; Wissenstransfer; Informationsverhalten; Theorie